Riedel's thyroiditis association with IgG4‐related disease. (7th October 2016) - Stan, Marius N.; Sonawane, Vikram; Sebo, Thomas J.; Thapa, Prabin; Bahn, Rebecca S.
Summary: Context: IgG4‐positive (+) plasma cells have been reported in both Riedel's thyroiditis (RT) and Hashimoto's thyroiditis (HT). These cells are the hallmark of IgG4‐related disease (IgG4‐RD). Objective: We sought to determine whether RT is part of IgG4‐RD spectrum. Design, Setting and Patients: This was a case–control study performed at a tertiary medical centre. We included RT cases from the period 1958 to 2008 that had sufficient paraffin‐embedded tissue for IgG4 immunostaining. Controls were patients with HT, age and gender matched, with similar pathology criteria. Main Outcome Measure: The main outcome measures were the intensity of the IgG4 staining and the clinical and histological correlates with IgG4‐RD. Results: Six pairs of RT and HT were analysed. The mean age was 44·7 years. In both groups, 5/6 cases had positive IgG4 staining. The mean number of IgG4 + cells/ HPF, normalized to the degree of inflammation, was 3·2 ± 3·0 SD (RT) vs 0·9 ± 0·7 (HT), P  = 0·15, for fibrotic areas and 2·1 ± 2·3 SD vs 1·0 ± 0·8 ( P  = 0·39) for areas with lymphoid aggregates. We found the number of IgG4 +  cells in RT to be inversely correlated with the duration of disease ( P  = 0·046). Three RT cases had associated comorbidities from the IgG4‐RD spectrum while none of the HT cases had such conditions. Conclusions: Riedel's thyroiditis is a component of IgG4‐RD with the density of the IgG4 +  lymphocytic infiltrate being time dependent. In this small study, we did not identify differences in IgG4 infiltration between RT and HT, minimizing the utility of this marker in RT diagnosis.